2018
DOI: 10.3389/fphar.2018.00664
|View full text |Cite
|
Sign up to set email alerts
|

Trimebutine Promotes Glioma Cell Apoptosis as a Potential Anti-tumor Agent

Abstract: Gliomas are the most common primary brain tumors with a usually fatal malignancy. They are associated with a poor prognosis although multiple therapeutic options have been available. Trimebutine is one of the prokinetic agents and it has been mainly used for treatment of disorders of the gastrointestinal (GI) tract such as irritable bowel syndrome. However, its effects on glioma cells remain unknown. Here, we used various concentrations of trimebutine to treat SHG44, U251, and U-87 MG human glioma/glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Bax is a member of the Bcl-2 protein family related to apoptosis. The ratio of pro- and anti-apoptotic molecules modulates apoptosis (Knudson and Korsmeyer, 1997; Fan et al, 2018). The results illustrated that the combination treatment significantly downregulated Bcl-2 levels but upregulated Bax levels (Figures 7D,E).…”
Section: Discussionmentioning
confidence: 99%
“…Bax is a member of the Bcl-2 protein family related to apoptosis. The ratio of pro- and anti-apoptotic molecules modulates apoptosis (Knudson and Korsmeyer, 1997; Fan et al, 2018). The results illustrated that the combination treatment significantly downregulated Bcl-2 levels but upregulated Bax levels (Figures 7D,E).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that opioid receptor expression in ovarian CSCs was not high and that opioid receptor agonists, such as DAMGO and dynorphin, had no effect, thereby demonstrating TM did not act through the opioid receptor in ovarian CSCs. It was also reported that TM acts as an opioid receptor agonist in glioma and glioblastoma cells, and inhibits cell proliferation at a range of 50–400µM without difference between glioma and glioblastoma cells by inhibiting ERK and AKT signaling pathways [ 41 ]. On the other hand, our data showed that TM could act on ovarian CSCs more selectively and effectively by the inhibition of stemness-related transcription factors, such as OCT3/4 and SOX2, through a blockade of the calcium and BKCa channels that are overexpressed in the ovarian CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding preclinical studies, TM was recently shown to be effective at maintaining upper and lower GI motor function in a peripheral CRF overlapping model with guinea pigs [ 33 ]. It is worth noting that apart from GI tract motility disorders, recent data suggest that TM may exert antitumor activities against gut and brain malignancies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%